Some Results on Neutrosophic Group - Amr Elrawy; Mohamed Abdalla; Mohammed A. Saleem (Journal of Mathematics)
We present the concept of a neutrosophic group without the use of an indeterminate element “I” in this paper. We also present a similar application to the fundamentals of group theory. We define and study the so-called level subgroups of a neutrosophic subgroup in order to characterize neutrosophic subgroups of finite cyclic groups in a similar way.